LONG-TERM RESULTS FOR THE TREATMENT OF PATIENTS WITH THE APPLICATION OF ORGAN-PRESERVING OPERATIONS IN PAPILARY THYROID CANCER - Korkelia, Alika (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
Іn order to analyse the changes in the structural and functional state of the thyroid gland, a group of 185 patients (67.8 %) were examined after the surgical treatment of papillary thyroid cancer. Of these, 94 patients belonged to the first group – the comparison group where thyroidectomy was performed, and 91 to the second – the main group where, mainly, organ-preserving operations were performed. The average follow-up was 6.5 ± 5.1 years (varied from 2 to 11 years. Hypoparathyroidism in patients receiving replacement therapy was observed in 20 (16.4 %) patients after thyroidectomy and only in 4 (6.3 %) patients after organ-preserving techniques (the differences are significant, p < 0.05). Side effects of replacement therapy were observed in 21 (17.2 %) patients after thyroidectomy and only in 4 (6.3 %) patients after organ-preserving techniques (the differences are significant, p < 0.05). Disease recurrence was detected in 4 (3.3 %) patients after thyroidectomy and in 1 (1.6 %) patient after organ-preserving techniques (the differences are not significant, р > 0.05). The use of organ-preserving approaches in the main group allowed improving functional results by reducing the frequency of hypothyroidism and side effects of replacement therapy, due to the preservation of thyroid secretion and its regulation, without worsening the results of relapse-free survival